Solid-liquid Extraction of Fatty Acids of Some Variety of Iranian Rice in Closed Vessel in the Absence and Presence of Ultrasonic Waves - Reza Babaei, Mohammad; Jabbari, Ali; Yamini, Yadollah (Asian Journal of Chemistry, 2010)
Extraction of the free fatty acids of four varieties of Iranian rice (Neda, Neamat, Fajr and Sahel) was done in closed vessels both in the absence and presence of ultrasonic waves. Then, the free fatty acids were converted into their methyl esters by the MeOH/BF3 reagent and were separated and determined by high-resolution gas chromatography equipped with flame ionization detector and a fused silica CBP-10 capillary column. The parameters influencing extraction efficiency, such as temperature, size of grains, volume ratio of methanol to chloroform as extracting solvent and extraction time, were optimized using a three level orthogonal array design with an OA9 (34) matrix. Furthermore, extraction efficiencies both in the presence and absence of ultrasound wave were compared at optimum conditions. The optimum conditions of T=80°C, mesh >100, t=35 min and volume ratio of methanol to chloroform, 2 : 1 were obtained in the absence of ultrasound wave. On the other hand, the time necessary for the quantitative extraction of free fatty acids in the presence of ultrasonic waves was reduced to 5 min. Based on the results, among the extraction parameters, temperature and size of grains had significant effects on the extraction efficiency and extraction yield was increased by an increase in temperature and a decrease in particle size. The amount of total fatty acids in these different rice varieties was in the range of 0.9-91.62% and Fajr variety had the greatest amount of free fatty acids.